Evaluation of the Response of HNSCC Cell Lines to γ-Rays and 12C Ions: Can Radioresistant Tumors Be Identified and Selected for 12C Ion Radiotherapy? - Ding, Lianghao; Sishc, Brock J.; Polsdofer, Elizabeth; Yordy, John S.; Facoetti, Angelica; Ciocca, Mario; Saha, Debabrata; Pompos, Arnold; Davis, Anthony J.; Story, Michael D. (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Thirty percent of patients will experience locoregional recurrence for which median survival is less than 1 year. Factors contributing to treatment failure include inherent resistance to X-rays and chemotherapy, hypoxia, epithelial to mesenchymal transition, and immune suppression. The unique properties of 12C radiotherapy including enhanced cell killing, a decreased oxygen enhancement ratio, generation of complex DNA damage, and the potential to overcome immune suppression make its application well suited to the treatment of HNSCC. We examined the 12C radioresponse of five HNSCC cell lines, whose surviving fraction at 3.5 Gy ranged from average to resistant when compared with a larger panel of 38 cell lines to determine if 12C irradiation can overcome X-ray radioresistance and to identify biomarkers predictive of 12C radioresponse. Cells were irradiated with 12C using a SOBP with an average LET of 80 keV/μm (CNAO: Pavia, Italy). RBE values varied depending upon endpoint used. A 37 gene signature was able to place cells in their respective radiosensitivity cohort with an accuracy of 86%. Radioresistant cells were characterized by an enrichment of genes associated with radioresistance and survival mechanisms including but not limited to G2/M Checkpoint MTORC1, HIF1α, and PI3K/AKT/MTOR signaling. These data were used in conjunction with an in silico-based modeling approach to evaluate tumor control probability after 12C irradiation that compared clinically used treatment schedules with fixed RBE values vs. the RBEs determined for each cell line. Based on the above analysis, we present the framework of a strategy to utilize biological markers to predict which HNSCC patients would benefit the most from 12C radiotherapy.